Switchable photoluminescence of CdTe nanocrystals by temperature-responsive microgels - Agrawal, M (Langmuir : the ACS journal of surfaces and colloids, 2008)
In the present study, we report a method for preparing a fluorescent thermosensitive hybrid material based on monodisperse, thermosensitive poly( N-isopropyl acrylamide) (PNIPAM) microgels covered with CdTe nanocrystals of 3.2 nm diameter. The CdTe nanocrystals were covalently immobilized on the surface of PNIPAM microgels. The chemical environment around the CdTe nanocrystals was modified by changing the temperature and inducing the microgel volume-phase transition. This change provoked a steep variation in the nanocrystal photoluminescence (PL) intensity in such a way that when the temperature was under the low critical solution temperature (LCST) of the polymer (36 degrees C) the PL of the nanocrystals was strongly quenched, whereas above the LCST the PL intensity was restored